Anxiety Disorders - The New Achievements 2021
DOI: 10.5772/intechopen.92079
|View full text |Cite
|
Sign up to set email alerts
|

Students Anxiety Experiences in Higher Education Institutions

Abstract: Students studying at higher education institutions face many challenges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…Besides, the work experience, positions (directors, assistants, supervisors, staff, and interns), GPA grade, number of times for admission, and monthly income. Based on the results, being a single female student aged 24-30 years, located in central Saudi Arabia, and earning a high monthly income was associated with better access to SPLE revision tools and resources, which equally influenced 23 found a strong and negative correlation between working hours and academic performance, whereby as the working hours increased, academic performance reduced. However, it was not found in the current study.…”
Section: Tools and Resources To Prepare For Saudi Pharmacist Licensur...mentioning
confidence: 97%
See 1 more Smart Citation
“…Besides, the work experience, positions (directors, assistants, supervisors, staff, and interns), GPA grade, number of times for admission, and monthly income. Based on the results, being a single female student aged 24-30 years, located in central Saudi Arabia, and earning a high monthly income was associated with better access to SPLE revision tools and resources, which equally influenced 23 found a strong and negative correlation between working hours and academic performance, whereby as the working hours increased, academic performance reduced. However, it was not found in the current study.…”
Section: Tools and Resources To Prepare For Saudi Pharmacist Licensur...mentioning
confidence: 97%
“…Regarding positions held, students in executive and nonexecutive positions may have numerous work-related responsibilities and workload that affects their preparedness and academic performance, including passing the SPLE tests. Students working more than 16 hr are likely to perform poorly and indicate lower academic performance than those working fewer hours 22,23. Okogbaa et al…”
mentioning
confidence: 99%
“…Although many studies suggest anxiety is highly prevalent among college students, recent studies also suggest that when anxiety increases, depression is likely also to increase (An et al, 2019; Cassady et al, 2019; Fava et al, 2006); this association has also persisted in adolescent and young adult populations (Jenkins et al, 2021; Young et al, 2006). Anxiety stemming from newfound pressures among college students studying at higher education institutions may lead to painful emotional depressive symptoms such as sadness, nervousness, worthlessness, helplessness, anger, and loneliness (AlKandari, 2020). Particularly, the factors contributing to students’ anxiety at higher education institutions (e.g., academic difficulty, financial pressure, employment, family responsibilities, and on-campus discrimination) may lead to depression (Andrews et al, 2014).…”
Section: Immigrant College Students With Precarious Versus Permanent ...mentioning
confidence: 99%
“…A previous study showed that students with anxiety disorder tend to avoid all social interaction, isolate themselves, and hardly seek help from others [59]. They do not have good friends where they can share all their problems with and prefer not to engage in any social activities [60][61][62]. They tend to doubt their future, and, in some cases, they get into trouble with others [61].…”
Section: Psycho-social Characteristicsmentioning
confidence: 99%